Gateway to the Golgi: molecular mechanisms of nucleotide sugar transporters. (August 2019) - Parker, Joanne L; Newstead, Simon
Highlights: Crystal structures highlight similarities between SLC35 transporters and the Drug and Metabolite Exporter superfamily. Specificity pockets were identified that reveal insights into nucleotide sugar recognition. Biochemical studies implicate a role for lipids in regulating SLC35 transporters within the secretory pathway. Abstract : The Golgi apparatus plays a central role in the secretory pathway as a hub for posttranslational modification, protein sorting and quality control. To date, there is little structural or biochemical information concerning the function of transporters that reside within this organelle. The SLC35 family of nucleotide sugar transporters link the synthesis of activated sugar molecules and sulfate in the cytoplasm, with the luminal transferases that catalyse their attachment to proteins and lipids during glycosylation and sulfation. A recent crystal structure of the GDP-mannose transporter has revealed key sequence motifs that direct ligand recognition and transport. Further biochemical studies unexpectedly found a requirement for short chain lipids in activating the transporter, suggesting a possible route for transport regulation within the Golgi.